Susceptibility of MMP3 gene polimorphism to coronary artery disease: A meta-analysis: MMP3 gene polymorphism to coronary artery disease - Liu, Wenwang (Journal of Medical Biochemistry, 2023)
Background: Conclusions on susceptibility of MMP3 -1612 5A/6A to morbid risk of coronary artery disease (CAD) are controversial. This meta-analysis aims to obtain the accurate relationship between them. Methods: Relevant literatures on susceptibility of MMP3 -1612 5A/6A to morbid risk of CAD published before July 2019 were searched in PubMed, Web of Science, Cochrane Library, CNKI, VIP and Wanfang. Data were extracted from eligible literatures and analyzed by RevMan5.3 and STATA12.0 for calculating OR and corresponding 95% CI. Study selection: A total of 18 literatures reporting MMP3 -1612 5A/6A and CAD were enrolled. Data extraction was conducted by two researches independently. Any disagreement was solved by the third research. Results: In recessive model (OR=1.3, 95%CI=1.2-1.64, P=0.03) and over-dominant model (OR=1.50, 95%CI=1.14-1.97, P=0.002), MMP3 -1612 5A/6A was correlated to susceptibility of CAD. Subgroup analysis uncovered that in different genetic models, MMP3 -1612 5A/6A was correlated to susceptibility of CAD in East Asian population (mainly Chinese population). Conclusions: MMP3 -1612 5A/6A is closely linked to morbid risk of CAD. Gene-environment interaction is the research focus in future analyses.